The ALS Health Profile Study: quality of life of amyotrophic lateral sclerosis patients and carers in Europe. - Jenkinson, C; Fitzpatrick, R; Swash, M; Peto, V (2000)
The measurement of functioning and well-being from the perspective of the patient has in recent years become central to the assessment of health and the evaluation of treatment regimes. The past decade has seen an enormous growth in the application of measures designed to assess quality of life in a vast array of medical specialties. However, the use of such measures in neurology has been relatively limited, and this has certainly been the case in amyotrophic lateral sclerosis (ALS). The European ALS Health Profile Study is a longitudinal survey of patients diagnosed with ALS or other motor neurone diseases in which patients are asked to complete questionnaires concerning their subjective health status. Data from clinical assessments are also collected. It is intended that the information collected will provide more systematic and detailed evidence of the impact of the disease from the perspective of the patient. This contribution documents results from baseline assessment obtained from data supplied by clinicians, carers and patients themselves. Three outcome measures are assessed in this paper: the SF-36, a generic measure of well being and functioning, the ALS Functional Rating Scale and the Carer Strain Index. The evidence presented here suggests that these measures provide a meaningful and valid picture of the impact of the disease. The data indicate that ALS has substantial adverse effects both upon the functioning and well being of patients and carers, as well as an association between the emotional health status of patients and carers, and between the physical health status of patients and carers.